Immunophenotyping of Peripheral Eosinophils Demonstrates Activation in Eosinophilic Esophagitis - Nguyen, Tammie (2011)
BACKGROUND AND AIM: Eosinophilic esophagitis (EoE) is a chronic inflammatory disorder characterized by upper gastrointestinal symptoms and the presence of high numbers of eosinophils in the esophagus. Although eosinophils in the esophagus have been found to be activated in subjects with EoE, detailed studies of intracellular signaling pathways involved in the mechanism of activation of eosinophils in EoE have heretofore been limited. The aim of the study was to assess whether any surface molecules or transcription factors are activated in peripheral eosinophils in subjects with EoE. METHODS: Eosinophils and CD3+ lymphocytes were identified directly from 50 μL of whole blood of EoE and control subjects. Using Hi-FACS, levels of surface activation markers, including CD66b, and intracellular phosphoepitopes, including phosphorylated forms of signal transducer and activator of transcription (phospho-STAT) 1 and 6, were measured within each cell subset. RESULTS: Levels of surface CD66b as well as levels of intracellular phospho-STAT1 and phospho-STAT6 in peripheral blood eosinophils were significantly higher for untreated subjects with EoE vs healthy controls (P <0.05). Levels of phospho-STAT1 and phospho-STAT6 in peripheral blood eosinophils were lower in subjects with EoE on therapy versus untreated subjects with EoE (P <0.05). CONCLUSIONS: Levels of phospho-STAT1 and phospho-STAT6, transcription factors involved in inflammatory processes, were both significantly higher in peripheral eosinophils from untreated (ie, newly diagnosed) subjects with EoE versus subjects with EoE on therapy, healthy controls. Blood-based measurements of CD66b and phospho-STAT levels in peripheral eosinophils may be beneficial for identifying EoE.